Dividend Payout Policy of Conventional Banking and Islamic Banking in Pakistan - Farhan Ahmed; Abdul Rafay; Afzal Ahmed (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
This paper investigates the difference between the dividend payout policy of Islamic banks and conventional banks in Pakistan for a period from 2012 to 2016 analyzing the data through regression using Least Square Method (OLS). Specifically, the study aims to study the impact of the profitability, liquidity, revenue growth and financial leverage on the dividend payout policy of the Islamic Banks and conventional banks of Pakistan and how Islamic banks dividend policy differs from conventional banks. This study concludes that the factors like liquidity and financial leverage should be considered and addressed accordingly, because these are key indicators to help policymakers and investors in assessing the performance of the Islamic Banking Industry. DOI: 10.15408/aiq.v10i1.6103